Pendampingan Penggunaan Teknologi Tepat Guna Mesin Pencetak Briket Arang sebagai Upaya Mengurangi Limbah Tempurung Kelapa - Kholiq Fadillah Amriansyah; Zaid Haidar Khairy; Joko Waluyo; Muhammad Sholeh; Dodik Prakoso Eko Hery Suwandojo; Eko Haryanto (Fakultas Sains Terapan, 2024)
Gunungkidul is an area where most of the area is a tourism destination. Especially in the Krambilsawit area of Saptosari Gunungkidul. In the village, there is one beach, Ngedan beach. Where the beach serves a lot of drinks from young coconut or food using a mixture of coconut, for example uwu sprinkled with grated coconut. One of the problems is the overflow of coconut shells or coconut shells. The solution to this problem includes processing the coconut shell into ordinary charcoal and has not been processed into briquettes. This potential becomes one of the activities of the community service team who are members of the Kosabangsa team to provide alternatives to making charcoal can be developed again, into charcoal briquettes using appropriate technology in the form of a charcoal briquette printing machine. The use of appropriate technology for this Charcoal Briquette Printing Machine can speed up the process of making charcoal briquettes. The method of implementing activities is carried out by making appropriate technology tools and socialising their use to the community. In implementing the activity, the implementation team applied several methods such as lectures, demonstrations, hands-on practice, and mentoring. The results of the implementation of the activity produced one appropriate technology for charcoal briquetting machines and socialisation of using appropriate technology for briquetting machines in the community.